2015
DOI: 10.1007/s10841-015-9791-4
|View full text |Cite
|
Sign up to set email alerts
|

Land management impacts on tree hole invertebrate communities in a Neotropical rainforest

Abstract: The Los Tuxtlas Biosphere Reserve in Southeastern Veracruz, Mexico represents the northernmost Neotropical lowland rainforest and has lost 84 % of its forests in the last forty years. Rich terrestrial and aquatic species communities are found throughout Neotropical forests, habitats increasingly threatened by land management practices. Plant-held waters, phytotelmata, are ecologically important discrete microhabitats harboring many specialist invertebrates and are abundant in tropical forests. In this study, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Recently, Richardson et al (2018) suggested that phytotelma fauna can be a useful bioindicator of ecosystem disturbance. This idea is supported by reports that AD impacts biomass and community structure of phytotelma invertebrates (Yanoviak et al, 2006;Khazan et al, 2015;Gossner et al, 2016). In some studies, changes in water PCPs have been linked to changes in communities of algae, archaea, bacteria, micro-and macroinvertebrates (Goffredi et al, 2011;Marino et al, 2011Marino et al, , 2013Carrias et al, 2012Carrias et al, , 2014Gossner et al, 2016;Louca et al, 2016Louca et al, , 2017Kratina et al, 2017).…”
Section: Resultsmentioning
confidence: 75%
“…Recently, Richardson et al (2018) suggested that phytotelma fauna can be a useful bioindicator of ecosystem disturbance. This idea is supported by reports that AD impacts biomass and community structure of phytotelma invertebrates (Yanoviak et al, 2006;Khazan et al, 2015;Gossner et al, 2016). In some studies, changes in water PCPs have been linked to changes in communities of algae, archaea, bacteria, micro-and macroinvertebrates (Goffredi et al, 2011;Marino et al, 2011Marino et al, , 2013Carrias et al, 2012Carrias et al, , 2014Gossner et al, 2016;Louca et al, 2016Louca et al, , 2017Kratina et al, 2017).…”
Section: Resultsmentioning
confidence: 75%
“…More detailed water chemistry measurements (e.g., nitrate, ammonium, and phosphate) are taken more rarely (but see Schmidl et al, 2008 ; Gossner, Lade, et al, 2016 ; Petermann et al, 2016 ). Characteristics of the surrounding environment such as wind speed and direction, canopy cover, and relative humidity are also rarely measured (but see Khazan et al, 2015 ; Petermann et al, 2020 ) but may be important to describe, for example, conditions for dispersal. Unfortunately, community studies rarely test and compare responses of individual species to environmental parameters (but see Schmidl et al, 2008 ; Gossner & Petermann, 2022 ).Thus, whether tree‐hole species have environmental limits and/or habitat preferences is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies on the effect of anthropogenic environmental change on tree‐hole communities suggest that there are strong negative effects of land‐use change (Khazan et al, 2015 ; Yanoviak et al, 2006 ), forest fragmentation (Nicholas, 2016 ), and forest management intensity (Gossner, Lade, et al, 2016 ; Petermann et al, 2020 , 2016 ), largely operating in an indirect way by affecting habitat and resource availability of the species (see e.g., Gossner, Lade, et al, 2016 ; Petermann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They do not account for habitat loss due to anthropogenic factors such as deforestation and urbanization. Further study is needed to adequately identify potential future habitats based on bioclimatic variables, urbanization, and vegetation modelling (Bowden et al 2011, Khazan et al 2015, Rogalski et al 2017, Kraemer et al 2019. Occurrence records tend to be clustered around areas easily accessed near roadways, towns and cities, and bodies of water near homes or areas of interest to collectors and observers (Newbold 2010).…”
Section: Discussionmentioning
confidence: 99%